Water Abundance of Dunes in Gale Crater, Mars From Active Neutron Experiments and Implications for Amorphous Phases. Issue 23 (11th December 2018) - Gabriel, T. S. J.; Hardgrove, C.; Czarnecki, S.; Rampe, E. B.; Rapin, W.; Achilles, C. N.; Sullivan, D.; Nowicki, S.; Thompson, L.; Litvak, M.; Mitrofanov, I.; Downs, R. T.
Abstract: We report the water abundance of Bagnold Dune sand in Gale crater, Mars by analyzing active neutron experiments using the Dynamic Albedo of Neutrons instrument. We report a bulk water‐equivalent‐hydrogen abundance of 0.68 ± 0.15 wt%, which is similar to measurements several kilometers away and from those taken of the dune surface. Thus, the dune is likely dehydrated throughout. Furthermore, we use geochemical constraints, including bulk water content, to develop compositional models of the amorphous fraction for which little information is known. We find the amorphous fraction contains ∼26‐ to 64‐wt% basaltic glass and up to ∼24‐wt% rhyolitic glass, suggesting at least one volcanic source for the dune material. We also find a range of hydrated phases may be present in appreciable abundances, either from the incorporation of eroded aqueously altered sediments or the direct alteration of the dune sand. Plain Language Summary: Dune sands in Gale crater are analagous to the globally distributed sands on Mars; however, their source and history, which is intimately related to their composition, is not well constrained. The minerals that compose the dune sands are determined and constrained from in situ analysis of samples, but much less has been determined for the amorphous (noncrystalline) component. These materials compose a sizable fraction of the dune material (40%) and can provide insight into the history of the dune material, including its interactions with water. We combine the analysis of several instruments onboard the Mars Science Laboratory Curiosity rover to constrain the noncrystalline component of Bagnold Dune sands in Gale crater. Particularly, we find the low water content of the dunes constrains the abundance of several amorphous materials and indicates that at least one, but potentially multiple, volcanic sources contributed to the dune. These results help provide a more holistic compositional description of the Bagnold Dune sands and potentially can be used to help determine the likely source regions in future studies. Key Points: Active neutron experiments show active dunes are the driest material in Gale crater Bagnold Dunes are dehydrated throughout; however, the presence of aqueously altered phases could not be ruled out Modeling of amorphous compositions shows the origin to be predominantly volcanic, potentially involving multiple or evolving sources